A critical review and commentary on recent progress of additive manufacturing and its impact on membrane technology - Qian, Xin; Ostwal, Mayur; Asatekin, Ayse; Geise, Geoffrey M.; Smith, Zachary P.; Phillip, William A.; Lively, Ryan P.; McCutcheon, Jeffrey R. (Journal of membrane science, 2022)
Membrane separations has been increasingly recognized as a key technology platform for improving the energy efficiency of many separations processes. Likewise, additive manufacturing (AM), or 3-dimensional (3D) printing as it is often called, is a rapidly emergent technology platform for manufacturing in many industrial sectors. It has become increasingly common to marry these two platforms to take advantage of the additive nature of 3D printing with the increasing need for membrane technology that is adaptable to separations needs. Conventional membrane manufacturing approaches, such as casting, typically result in thick membranes that limit productivity and potentially waste material in a non-performing support layer. Interfacial polymerization (IP) offered a new vision for thin-film composite desalination membranes, yet it was limited to certain chemistries while exhibiting other drawbacks. Additive manufacturing offers certain benefits over these techniques to membranes, including the ability to expand the library of materials that can be processed while also offering a degree of customization that is impossible in conventional manufacturing. This review article evaluates an increasing body of literature on using printing to make membranes and considers the limitations and opportunities for printing to enhance existing membrane technology and expand the reach of membranes into other industries. We also provide a perspective from leading experts in membrane technology to see where there are opportunities to use printing in different membrane science disciplines. [Display omitted] •We provide a historical perspective of membrane manufacturing and its limitations.•We review the recent applications of additive manufacturing to membrane technology.•We compare 3D printing with conventional methods in terms of key manufacturing metrics.•Future challenges and perspectives of 3D printing on membrane technology are proposed.•The corresponding author has multiple pending patents on 3D printed membrane technology.